PEMBUATAN EDIBLE FILM DARI PATI SUKUN DAN EKSTRAK KULIT JERUK SEBAGAI SUMBER BELAJAR MATERI POLIMER - memi rozalina; yusbarina yusbarina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
The use of plastic can cause environmental pollution and risk the health of consumers. One of ways to solve this problem is the use of biodegradable packaging food is that edible film. Raw material for preparing edible film can be derived from starch, one of them is Breadfruit starch. Edible film can protect the packaged product of the oxidation process by adding orange skin extract. This research aimed at knowing physical and chemical characteristics of edible film of breadfruit starch with the addition of orange skin extract and the implementation of the source of student learning on Polymer material. Edible film was prepared from breadfruit starch with variation by adding 0, 2, 4 and 6 grs orange skin extract. Physical analysis was tested by using Water Vapor Transmission Rate and chemical analysis was tested by using Water Content and Antioxidant Activity Tests. Research findings showed that along with increasing the composition of orange skin extract, edible film was impairing of water vapor transmission rate, and increasing of water levels and antioxidant activity. Research product appropriateness of preparing edible film of Breadfruit starch with the addition of orange skin extract as the source of student learning on Polymer material was on the category of good (88.33%).Keywords: Edible Film, Starch, Breadfruit, Extract, Orange Skin